Genomic landscape of metastatic breast cancer and its clinical implications - Angus, Lindsay (Nat Genet, 2019)
Whole genome sequencing (WGS) of prospectively collected tissue biopsies of 442 metastatic breast cancer (mBC) patients reveals that, compared to primary BC, tumour mutational burden (TMB) doubled, relative contributions of mutational signatures shifted, and mutation frequency of six known driver genes increased in mBC. Significant associations with pre-treatment were observed as well. The contribution of mutational signature 17 was significantly enriched in patients pre-treated with 5-FU, taxanes, platinum and/or eribulin, whereas the here identified de novo mutational signature I was significantly associated with pre-treatment containing platinum-based chemotherapy. Clinically relevant subgroups of tumours were identified exhibiting either homologous recombination deficiency (13%), high TMB (11%) or specific alterations (24%) linked to sensitivity to FDA-approved drugs. This study provides important novel insight into the biology of mBC and identifies clinically useful genomic features for future improvement of patient management.